The Roles a Teacher Has to Play in Teaching English as a Foreign Languge - agustina sri hafidah (Jurnal Penelitian Pendidikan, 2009)
It is true that teacher’s roles are very important in teaching learning process, especially in teaching learning English. Teaching English is an art which can be divided into two parts: the mastery of the theory and the mastery of the practice. The mastery of the art must be a matter of ultimate concern; there must be nothing more important in the world than art. Teaching English is also an art. English may cover a wide range of topics such as stages of the lesson, classroom management, lesson planning, and other topics. This paper will share a few of ideas of how to be a good teacher who master in the art of teaching English. These responses imply that aside from the teacher’s character and personality, which affect his or her teaching, the teacher’s support with students also plays an important role in the success of learning.